FORMULASI YOGHURT SEBAGAI LOSIO PEMBERSIH WAJAH DENGAN MENGGUNAKAN VARIASI EMULGATOR - Faradiba Faradiba; Nursiah Hasyim; Andi Fitriyati (As-Syifaa Jurnal Farmasi, 2010)
Yoghurt formulation as facial cleansing lotion has been done in which the emulsifier were nonionic (tween 60 and span 60), amine soap (triethanolamin and stearic acid), and detergent (sodium lauryl sulfate) respectively. The aim was to determine the most optimum stabilty formulation. The evaluation was carried out before and after accelerated condition in 5ºC and 35ºC respectively for 10 cycles.Organoleptic, creaming volume, emulsion type, dirpersed globul, viscosity, and yield value were observed. The result of organoleptik showed that there were no change in color and smell, creaming volume and dispersed globul before and after accelerated condition. Statystic analyses foward the viscosity in formula I was apparently indifferent mean while the second and the third formula were different in viscosity. statystic analyses foward the yield value in formula I was apparently indifferent and the second  was different mean while  the third formula very different in yield value. Formula I showed the most minimum alteration in rheogram . Of it the has taken that the most stable emulsion was nonionic emulsifier (tween 60 and span 60).Key Words : Facial cleansing lotion, Yoghurt, Emulgator